Continued Elevation of Interleukin-18 and Interferon-γ After Initiation of Antiretroviral Therapy and Clinical Failure in a Diverse Multicountry Human Immunodeficiency Virus Cohort. (27th July 2016) - Balagopal, Ashwin; Gupte, Nikhil; Shivakoti, Rupak; Cox, Andrea L.; Yang, Wei-Teng; Berendes, Sima; Mwelase, Noluthando; Kanyama, Cecilia; Pillay, Sandy; Samaneka, Wadzanai; Santos, Breno; Poongulali, Selvamuthu; et al.
Abstract: Background.  We assessed immune activation after antiretroviral therapy (ART) initiation to understand clinical failure in diverse settings. Methods.  We performed a case-control study in ACTG Prospective Evaluation of Antiretrovirals in Resource-Limited Settings (PEARLS). Cases were defined as incident World Health Organization Stage 3 or 4 human immunodeficiency virus (HIV) disease or death, analyzed from ART weeks 24 (ART24) to 96. Controls were randomly selected. Interleukin (IL)-6, interferon (IFN)-γ-inducible protein-10, IL-18, tumor necrosis factor-α, IFN-γ, and soluble CD14 (sCD14) were measured pre-ART and at ART24 in plasma. Continued elevation was defined by thresholds set by highest pre-ART quartiles (>Q3). Incident risk ratios (IRRs) for clinical progression were estimated by Poisson regression, adjusting for age, sex, treatment, country, time-updated CD4 + T-cell count, HIV ribonucleic acid (RNA), and prevalent tuberculosis. Results.  Among 99 cases and 234 controls, median baseline CD4 + T-cell count was 181 cells/µL, and HIV RNA was 5.05 log10 cp/mL. Clinical failure was independently associated with continued elevations of IL-18 (IRR, 3.03; 95% confidence interval [CI], 1.27–7.20), sCD14 (IRR, 2.17; 95% CI, 1.02–4.62), and IFN-γ (IRR, 0.08; 95% CI, 0.01–0.61). Among 276 of 333 (83%) who were virologically suppressed at ART24, IFN-γ was associated with protection from failure, but the association with sCD14 was attenuated. Conclusions.  Continued IL-18 and sCD14 elevations were associated with clinical ART failure. Interferon-γ levels may reflect preserved immune function.